2018
DOI: 10.1002/chem.201705597
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Generation of a Carbanion: The Key Step of PTC Reaction Directly Observed by Second Harmonic Generation

Abstract: We present the first unambiguous evidence of the interfacial mechanism of phase-transfer catalysis (PTC) by direct observation of the formation of carbanions in the interfacial region between the aqueous and the organic phase by using a surface-sensitive spectroscopic method known as second harmonic generation (SHG). Ion exchange of carbanions adsorbed at the surface after addition of lipophilic tetraalkylammonium salts (TAA) to organic phase and transport of the lipophilic ion-pairs to the organic phase is ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…SHG spectroscopy has been used previously to study a variety of catalytic systems at interfaces including monitoring adsorption of gaseous reactants at solid surfaces and even identifying reaction intermediates in liquid phases (when the intermediates have a resonance at the second harmonic wavelength). 25,26 This surface-selectivity makes SHG spectroscopy especially useful for studying electrochemical systems. EFISHG is a form of SHG in which the response of a charged interface requires consideration of an additional static electric eld(s) (E DC ), eqn (3).…”
Section: Introductionmentioning
confidence: 99%
“…SHG spectroscopy has been used previously to study a variety of catalytic systems at interfaces including monitoring adsorption of gaseous reactants at solid surfaces and even identifying reaction intermediates in liquid phases (when the intermediates have a resonance at the second harmonic wavelength). 25,26 This surface-selectivity makes SHG spectroscopy especially useful for studying electrochemical systems. EFISHG is a form of SHG in which the response of a charged interface requires consideration of an additional static electric eld(s) (E DC ), eqn (3).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the catalysts applied at 1 mol % displayed a range of activities from negligible effect of tetramethylammonium chloride ( 1 ) and benzyldimethyl­(2-hydroxyethyl)­ammonium chloride ( 3 ) to moderate activity of benzyltriethylammonium chloride ( 2 ) and 18-crown-6 ( 7 ) and to highly efficient tetraphenylarsonium chloride hydrochloride hydrate ( 6 ), tetrabutylammonium chloride ( 4a ), and methyltrioctylammonium chloride ( 5 ) . Although origin of the observed differences in activity was not entirely clear, we believed that lipophilicity of the catalyst cation, which forms an ion pair entering the organic phase, is a predominant factor . Considering extractive mechanism of the phase transfer catalysis, at the interfacial region lipophilic cation of the catalyst forms an ion pair with inorganic anion dissolved in the aqueous phase, which then enters the organic phase and reacts, giving an organic product and a new ion pair with leaving group of the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, interfacially generated DCC being in close vicinity to these carboxylates adds to the double bond even in the absence of the PT catalysts. Addition of TAA salts only slightly improves the yields [33,34]…”
Section: Specific Features Of Generation and Reactions Of Dichlorocar...mentioning
confidence: 99%
“…In order to achieve that, the proper surface-specific experimental method is needed. We have recently found that surface-specific spectral technique-surface second harmonic generation (SHG)-can be used after proper modification for this purpose [34]. In this technique the surface between two immiscible liquids is illuminated with focused high intensity fs-laser pulses.…”
Section: Direct Observation Of Interfacially Generated Carbanionsmentioning
confidence: 99%